Evaluation of Factors Influencing Bicycle Accidents as an Effort to Improve Transportation Safety and Sustainability in Surabaya City - Nika Devi Permata Wijaya; Bambang Tri Leksono (Pusat Publikasi Nusantara, 2025)
Traffic accidents involving cyclists remain a pressing urban safety issue in Indonesia, where mixed traffic patterns increase risks for non-motorized road users. The growing number of cyclists in Surabaya underscores the need for proper infrastructure planning that ensures both safety and mobility efficiency. This research aims to analyze the factors contributing to bicycle accidents and propose appropriate bicycle lane design recommendations based on road function, geometric characteristics, and traffic performance. The study employs a quantitative-descriptive method, combining accident data analysis, road geometry assessment, and Level of Service (LOS) evaluation. Findings reveal that cyclist accidents are predominantly influenced by socioeconomic factors, low safety awareness, lack of protective equipment, and insufficient road space allocation. Young cyclists with minimal safety discipline are particularly vulnerable, especially during morning hours on arterial roads with high traffic volumes. Based on the LOS and road classification, arterial roads such as Ahmad Yani, Darmo, and Ngagel require Type C (bike road) lanes with full physical separation from motorized traffic, while collector roads such as Ir. H. Soekarno, Kedung Cowek, and Mastrip are suitable for Type A (bike lane) configurations located alongside vehicle lanes. These results highlight that context-sensitive bicycle lane design—tailored to traffic characteristics and road capacity—is essential for promoting cyclist safety, reducing accident rates, and supporting sustainable urban mobility in Surabaya.